2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683855
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Time Markov Chain Model for High Throughput Bidirectional Fano Decoders

Abstract: Abstract-The bidirectional Fano algorithm (BFA) can achieve at least two times decoding throughput compared to the conventional unidirectional Fano algorithm (UFA). In this paper, bidirectional Fano decoding is examined from the queuing theory perspective. A Discrete Time Markov Chain (DTMC) is employed to model the BFA decoder with a finite input buffer. The relationship between the input data rate, the input buffer size and the clock speed of the BFA decoder is established. The DTMC based modelling can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A single UFA/BFA decoder with a finite input buffer can be treated as a D/G/1/B queue [21], in which D means that the input data rate is deterministic, G means that the decoding time is generic, 1 means that there is one decoder and B is the number of codewords the input buffer can hold. The state of the Fano decoder is represented by the input buffer occupancy or queue length when a codeword just finishes decoding, which is measured in terms of branches or information bits stored in the buffer.…”
Section: Dtmc Based Modeling On Single Ufa/bfamentioning
confidence: 99%
See 1 more Smart Citation
“…A single UFA/BFA decoder with a finite input buffer can be treated as a D/G/1/B queue [21], in which D means that the input data rate is deterministic, G means that the decoding time is generic, 1 means that there is one decoder and B is the number of codewords the input buffer can hold. The state of the Fano decoder is represented by the input buffer occupancy or queue length when a codeword just finishes decoding, which is measured in terms of branches or information bits stored in the buffer.…”
Section: Dtmc Based Modeling On Single Ufa/bfamentioning
confidence: 99%
“…The accuracy of the model degrades as B gets smaller. However, a very short input buffer will not be adopted according to the trade-off between area and decoding throughput as discussed in [21]. Additionally, it has also been found that the accuracy of the model does not depend on the relationship between M and N (i.e., M >N, M = N or M <N) as long as the input buffer size is large enough.…”
Section: Validation Of the Dtmc Modelmentioning
confidence: 99%